Anticancer profile of coumarin 6-based Ir(iii) photocatalysts under normoxia and hypoxia by ROS generation and NADH oxidation - Yadav A.K.; Upadhyay A.; Bera A.; Kushwaha R.; Mandal A.A.; Acharjee S.; Kunwar A.; Banerjee S. (My University, 2025)
Herein, we have designed, synthesized, and characterized two novel coumarin-6-based Ir(iii) photo-catalysts viz. [Ir(CO6)2(dppz)]Cl (Ir1) and [Ir(CO6)2(aip)]Cl (Ir2), where CO6 = coumarin 6, dppz = dipyrido[3,2-a:2′,3′-c]phenazine, and aip = 2-(anthracen-9-yl)-1H-imidazo[4,5-f][1,10]phenanthroline. Coumarin 6 introduced a green light absorption property. When exposed to green light, complexes Ir1 and Ir2 demonstrated catalytic NADH photo-oxidation with a TOF of ca. 840-1000 h−1 in PBS, comparable to or higher than the highest achieved TOF with previously reported Ir(iii)-based photo-catalysts for NADH oxidation. Ir1 and Ir2 also generated 1O2 on green light irradiation. Both the complexes showed remarkable photo-toxicities against human lung adenocarcinoma cells (A549) and human cervical cancer cells (HeLa) with the IC50 and PIs (dark IC50/light IC50) in the range of 0.5-1.6 μM and >28-71, respectively. Interestingly, these complexes did not show any notable toxicities toward the normal human bronchial epithelial (BEAS-2B) cell line under dark conditions. The selectivity index (SI = light IC50 in normal cells/light IC50 in cancer cells) of Ir1 and Ir2 for the killing of cancer cells was in the range of 7-19. Moreover, Ir1 and Ir2 also showed good phototoxicity against A549 cancer cells under hypoxic conditions, revealing their potential for hypoxic tumor treatment. The mechanistic investigation of the most potent complex Ir2 in A549 cells revealed that it localized in the mitochondria, generated ROS and oxidized NADH during light exposure, ultimately causing cell apoptosis via mitochondrial depolarization. This strategy of killing cancer cells by combining type-I and type-II mechanisms, i.e. via NADH oxidation, H2O2, ˙OH, and 1O2 generation, could provide efficient photo-activated chemotherapy. © 2024 The Royal Society of Chemistry.